C1 2015 10 Edexcel

image

(a)

Write:

\displaystyle f'(x) = \frac 3 2 x^{1/2} - \frac 9 4 x^{-1/2} + 2

Then:

\begin{align*}f(x) &= \int f'(x) \mathrm dx \\ & = \frac 3 2 \times \frac {x^{3/2}} {\frac 3 2} - \frac 9 4 \frac {x^{1/2}} {\frac 1 2} + 2x + C \\ & = x^{3/2} - \frac 9 2 x^{1/2} + 2x + C\end{align*}

At x = 4 we have:

\displaystyle y = 4^{3/2} - \frac 9 2 \times 4^{1/2} + 2 \times 4 = 8 - 9 + 8 + C = 7 + C = 9

So C = 2. Hence:

\displaystyle f(x) = x^{3/2} - \frac 9 2 x^{1/2} + 2x + 2

(b)

The line 2y + x = 0 has gradient -\dfrac 1 2. The normal at P therefore has gradient -\dfrac 1 2, so the tangent at P has gradient 2. So, we have:

\displaystyle \frac 3 2 \sqrt x - \frac 9 {4 \sqrt x} + 2 = 2

So:

\displaystyle \frac 3 2 \sqrt x = \frac 9 {4 \sqrt x}

So the x-coordinate of P is given by:

\displaystyle x = \frac 2 3 \times \frac 9 4 = \frac 3 2

1 Like

:innocent: